1966
DOI: 10.1115/1.3624979
|View full text |Cite
|
Sign up to set email alerts
|

Stresses Around an Elliptical Hole in a Finite Plate Subjected to Axial Loading

Abstract: A photoelastic solution of the distribution of stresses around a centrally located elliptical hole in a plate of finite width subjected to uniform axial loading is presented in this paper. Stress distributions at the boundaries are given for a wide range of the parameters, and stress-concentration factors have been computed for the points of maximum tensile and of maximum compressive stress. Comparisons are made with available theoretical solutions. Some appreciable discrepancies are pointed out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Facing the aforementioned situations, based on the stress distribution of a tension infinite plate with an elliptical hole, applying balance conditions with section method, after integrating and solving equations, initial SCF expressions for a tension strip with an eccentric elliptical hole, and the special situation with a central elliptical hole, can be obtained, and then explicit expressions are proposed by a smart revision. Compared with finite element analysis (FEA) results and available test data [8][9][10]15] , these expressions are shown to have good accuracy. And the application of these deduced expressions at extremes, e.g., for a crack, is also demonstrated to be good.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Facing the aforementioned situations, based on the stress distribution of a tension infinite plate with an elliptical hole, applying balance conditions with section method, after integrating and solving equations, initial SCF expressions for a tension strip with an eccentric elliptical hole, and the special situation with a central elliptical hole, can be obtained, and then explicit expressions are proposed by a smart revision. Compared with finite element analysis (FEA) results and available test data [8][9][10]15] , these expressions are shown to have good accuracy. And the application of these deduced expressions at extremes, e.g., for a crack, is also demonstrated to be good.…”
Section: Introductionmentioning
confidence: 89%
“…Theoretical study on a tension strip with an eccentric elliptical hole was done by Nishida [8] , but the error of corresponding formula is relatively large. A photo-elastic test for a tension strip with a central elliptical hole was conducted by Durelli et al [15] . However, the application ranges of these theoretical studies are limited, or no explicit expression is available from the experimental investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Figures 23 and 24 show the stresses in the x-direction on the y-axis of sample-1 and -2, respectively. As the author could not find stresses computed analytically in papers Inglis (1913) 4.00 5.00 Infinite plate Ishida (1955) 4.43 6.50 Infinite strip Durelli et al (1966) 4.69 6.17 Finite plate published so far, stresses measured by photo-elastic experiments are put in the figures. Nishida et al (1966) reported the stresses on the y-axis.…”
Section: Plates With An Oval Hole Under Tensionmentioning
confidence: 98%
“…Ishida (1955) found the stresses on the y-axis and the hoop stresses of infinite plates. Durelli et al (1966) obtained the stresses by photo-elastic experiments. Table 2 shows the stress concentration factors in the papers mentioned above.…”
Section: Plates With An Elliptical Hole Under Tensionmentioning
confidence: 99%
“…Hence, the prediction of K t still plays a significant role in studying the failure of corroded CI pipes. In the classical mechanics of materials, theoretical solutions of SCF can only be obtained for some regularly sharped holes (e.g., circular and elliptical) on plate of uniform thickness [3,4]. Nevertheless, most corrosion pits appear to be non-through wall type and cannot be expressed by a hole-based SCF solution.…”
Section: Introductionmentioning
confidence: 99%